Latin American Textualities : History, Materiality, and Digital Media - Reynolds, Andrew R.; Allen, Heather J. (Book collections on Project MUSE., 2018)
Textuality is the condition in which a text is created, edited, archived, published, disseminated, and consumed. "Texts," therefore, encompass a broad variety of artifacts: traditional printed matter such as grammar books and newspaper articles; phonographs; graphic novels; ephemera such as fashion illustrations, catalogs, and postcards; and even virtual databases and cataloging systems.\ Latin American Textualities is a wide-ranging, interdisciplinary look at textual history, textual artifacts, and digital textualities across Latin America from the colonial era to the present. Editors Heather J. Allen and Andrew R. Reynolds gather a wide range of scholars to investigate the region's textual scholarship. Contributors offer engaging examples of not just artifacts but also the contexts in which the texts are used. Topics include Guamán Poma's library, the effect of sound recordings on writing in Argentina, Sudamericana Publishing House's contribution to the Latin American literary boom, and Argentine science fiction. Latin American Textualities provides new paths to reading Latin American history, culture, and literatures.